Examining The Illocutionary Acts in The Paddington Movie and Their Influence on Cultivating The Profile of Pancasila Students - Nuraini, Safrina; Widyawati, Wiwin; Wulandari, Rifa Suci (ELTALL: English Language Teaching, Applied Linguistic and Literature, 2024)
The use of speech acts is an integral part of everyday conversation, representing actions rather than mere statements about objects. The relationship between speech acts and a speaker's character is closely intertwined, as one's character influences the type and manner of speech used. In Indonesia, the government emphasizes character development, evident in the Minister of Education and Culture's initiative, the Pancasila Student Profile, aimed at shaping Indonesian students' characters. This study focuses on analyzing speech acts, particularly Illocutionary speech acts within the Paddington Movie, and their role in cultivating the Pancasila Student Profile. Employing a descriptive qualitative approach, this research relies on George Yule's and John R. Searle's theories on speech acts. Data collection involves documenting instances from the "Paddington" movie. Results indicate the identification of five types of Illocutionary speech acts in the film: assertive (24%), directives (39.6%), commissive (5.6%), expressive (28%), and declaratives (1.8%). Moreover, the analysis reveals expressions in the script that align with the values encapsulated in the Pancasila Student Profile. Overall, the Illocutionary speech acts throughout the Paddington movie contribute to the construction of the Pancasila Student Profile through various utterances.